Predatory Encounters of Yllenus Arenarius (Araneae, Salticidae) with Flies (Diptera) - Bartos, Maciej (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2010)
Predatory behaviour of Yllenus arenarius hunting flies (Diptera) was studied. The general spider’s approach and capture was typical for salticids hunting prey that has high ability to escape. Two modes of approach in close proximity of prey were observed. One was typical for the majority of predatory encounters where the spider’s velocity was significantly reduced with decreasing distance to prey. Stalk and movement masking were typical for this type of approach. Second mode occurred sporadically and was characterized by a high spider’s velocity that was not reduced in the vicinity of the prey.